Penyebab Kuatnya Nilai Islam Dalam Masyarakat Tatar Sunda - Naila Soima Kamila (Priangan: Journal of Islamic Sundanese Culture, 2022)
People with a mindset will basically follow the people around them, in other words, the group that makes up their majority will be able to influence the mindset of the people around them. Likewise with Islam, when Islam begins to be widely known to outsiders, those who actually have not been touched by Islamic teachings but hear about Islam, will find out for themselves and convert to Islam on their own without coercion. In its development, Islam does have special features. Examining the spread in the Sunda Tatat cannot only focus on one source to find out about the truth from that source from other sources. In history, very little Islam shed blood in its spread. For this reason, many researchers have examined the reasons why Islam was spread without coercion and the people who accepted it voluntarily were able to survive until now. As for who spread Islamic teachings and teachings in Tatar Sunda, it is already known who and how the story of his da'wah was, but it does not rule out the existence of many propagators of Islam who have not been revealed by historians because of the personal desire to spread Islam from the individuals themselves without being known to the public. By research that focuses on the people who have contributed to spreading the religion of Islam, so little by little those various figures are able to be revealed.